Inactivation of Venezuelan Equine Encephalomyelitis Virus by γ-Radiation - Reitman, Morton (1967)
Exposure of Venezuelan equine encephalomyelitis (VEE) virus (at -70 C) to 6 × 10(6) r γ-radiation ((60)Co) resulted in loss of lethality for young adult mice and guinea pigs, and loss of capacity to produce plaques or cytopathic effects in tissue culture. The suckling mouse was more sensitive for detecting live virus in radiated suspensions than was the adult mouse or guinea pig. Live virus was demonstrable in preparations exposed to 6 × 10(6) r but not in suspensions exposed to 8 × 10(6) r and more. The rate of inactivation of VEE virus by γ-radiation was an exponential function of the dosage.